2022
DOI: 10.1039/d2nr03754h
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-complexed SnO2 electron transport layer for high-efficiency n-i-p perovskite solar cells

Abstract: Effective electron transport layer (ETL) plays a pivotal role in suppressing nonradiative recombination at interface, as well as promoting perovskite crystallization to facilitate electron extraction in solar cells (PSCs). Herein,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Owing to the large surface area and significant internal van der Waals force of nanoparticles, they tend to agglomerate, forming irregular colloids. 25 According to previous studies, 26 oxygencontaining compounds with lone pair electrons can coordinate with Sn. Oxygen contributes these lone pair electrons to the empty d orbit of the metal atom, resulting in the formation of a metal−oxygen complex.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Owing to the large surface area and significant internal van der Waals force of nanoparticles, they tend to agglomerate, forming irregular colloids. 25 According to previous studies, 26 oxygencontaining compounds with lone pair electrons can coordinate with Sn. Oxygen contributes these lone pair electrons to the empty d orbit of the metal atom, resulting in the formation of a metal−oxygen complex.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…The molecular structure of AMSA is depicted in Figure S1a. Owing to the large surface area and significant internal van der Waals force of nanoparticles, they tend to agglomerate, forming irregular colloids . According to previous studies, oxygen-containing compounds with lone pair electrons can coordinate with Sn.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[15b] In order to study the effect of PAA on the conductivity of the SnO 2 films, the dark currentvoltage (I-V) curve confirmed that the ohmic conductivity of SnO 2 /PAA-2 was higher than the control (Figure 3b), which can be associated to the reduced surface defects of SnO 2 film and the improved free electrons donated by the PAA modification, also pushes the ETL/perovskite interfacial electron transport, and improves the short-circuit current density (J sc ) for PSCs. [19,29] However, in case of SnO 2 /PAA-1, the excessive insulation of PAA affects the conductivity of the relevant device, which may concur with a decreased device performance, and the SnO 2 / PAA-3 with the least PAA modification agent has a slight impact on the conductivity and corresponding device PCE, which will be discussed in the following section.…”
Section: Optical Electrochemical Propertiesmentioning
confidence: 99%
“…Many water‐soluble polymers have been utilized to suppress the issue of SnO 2 agglomeration in the suspension while passivate defects of both SnO 2 and perovskite. Examples include polyethylene glycol (PEG), [9c,16] poly(ethylene glycol) diacrylate (PEGDA), [17] polyethylene oxide‐polypropylene oxide‐polyethylene oxide (P123), [18] heparin potassium (HP), [9b] poly(amidoamine) (PM) dendrimer, [19] polyvinylpyrrolidone (PVP) and its derivatives, [20] polyacrylamide (PAM), [21] and ammonium polyacrylate (PANH 4 ), [22] etc. were reported, and mainly of them were uniformly dispersed in SnO 2 colloidal ink and promote the nanoparticle disaggregation in the ink, interact with both tin and oxygen dangling bonds, as well as hydroxyl groups in SnO 2 surface, complex with uncoordinated Pb 2+ to passivate defects, strengthen the interface contact between the ETL and the perovskite layer, and so on.…”
Section: Introductionmentioning
confidence: 99%